Formative factors affecting the performance of the communicator in Islamic media - Rababah, Mohammad; Abu Ghazaleh, Mohammad (Jordan Journal of Islamic Studies, 2023)
The aim of this study was to identify the formative factors affecting the performance of the communicator and their role in convincing the public of the content of the communication by studying these factors in the light of the Holy Qoran and recent media studies. The researchers used the extrapolative approach based on extrapolating the vocabulary from their scientific sources; Legitimacy, connectivity, etc. and comparative deductibility, which tends to analyses legitimate texts with communication connotations, to derive the formative factors of the communicator from them, and to compare the semantics of the texts with what is confirmed by the emerging empirical studies. The research produced a number of findings, including: Five factors have a direct impact on the performance of the contact person: Communicator’s intention, skills, reliability, level of knowledge and being model. The of coding in modern media terms corresponds to the skill of statement in the Quranic concept. The impact of the discord between credibility and the idea for the public could be reduced by certain actions. The deposits and interests of the social system could influence the credibility of the contact person. and other findings and recommendations.